Transparent thermal insulation coating and preparation method thereof
By uniformly dispersing ATO/TiO2 composite nanoparticles in the magnesium fluoride matrix, the problems of insufficient transparency and thermal insulation performance of existing transparent thermal insulation coatings are solved, and a coating with high transparency and good thermal insulation effect is achieved. in construction and automotive glass.
Patent Information
- Application Number
- CN202411461113.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-20
AI Technical Summary
After adding nano or submicron powders, the transparency of existing transparent heat insulation coatings is reduced and the thermal insulation performance is insufficient. In particular, the dispersion of nano powders such as indium tin oxide (ITO) and zinc oxide (ZnO) in the coating is poor, which affects the influence of The application effect of the coating.
Magnesium oxide fluoride (Mg(OF)x) is used as the matrix to uniformly disperse ATO/TiO2 composite nanoparticles, and two-component hollow structure ATO/TiO2 composite nanopowder is prepared by hydrothermal method and template-free method, and the ATO/TiO2 composite nanopowder with two-component hollow structure is prepared in Mg( The OF)x matrix is added to improve the dispersion and viscosity of nanoparticles by controlling the amount of diethylene triamine and polyethylene glycol, and a coating with high transparency and good thermal insulation effect is formed.
It achieves a transmittance of more than 85% and a heat insulation effect of more than 10°C while maintaining high transparency, and is suitable for construction and automotive glass fields.
Smart Images

Figure CN119161752A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a transparent heat-insulating coating and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasing awareness of environmental protection, energy conservation and emission reduction have become important issues in all walks of life. In fields such as architecture and automobiles, glass windows, as the main way of lighting and ventilation, provide a good view and indoor comfort, but also become the main channel for heat transfer. Therefore, the development of a transparent thermal insulation coating that can maintain high light transmittance and effectively isolate solar thermal radiation has become the key to solving this problem.
[0003] Research has found that adding some nano or submicron powders, such as indium tin oxide (ITO), tin oxide (SnO2), zinc oxide (ZnO), etc., to the coating has unique physical and chemical properties, such as high specific surface area and high surface activity, and has excellent performance in heat insulation, light transmission, and UV resistance. Therefore, its development has become an important direction for transparent thermal insulation coatings. At present, some studies have used powders such as indium tin oxide (ITO), tin oxide (SnO2), zinc oxide (ZnO), etc., and mixed them with acrylic resins to obtain transparent thermal insulation coatings. By utilizing the good light absorption properties of these materials, the thermal insulation effect is improved.
[0004] On the other hand, the transparency of transparent heat-insulating coatings is also very important. By adding nano or submicron powders to the coating, the transparency of the coating is more or less reduced. In particular, studies have found that nano powders such as indium tin oxide (ITO), tin oxide (SnO2), zinc oxide (ZnO), and titanium oxide (TiO2) have poor dispersion in coatings, which further reduces the transparency of the coating when it is used to prepare transparent heat-insulating coatings on transparent substrates. Summary of the invention
[0005] The purpose of the present invention is to provide a transparent heat-insulating coating and a preparation method thereof, which takes into account both transparency and heat insulation to form a coating with high permeability and high heat insulation effect, so that it can be used in automobiles, construction industries, etc.
[0006] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical scheme.
[0007] First, the present invention provides a transparent heat-insulating coating, wherein the coating is magnesium oxyfluoride Mg (OF) x As the matrix, in the Mg(OF) xATO / TiO2 composite nanoparticles are uniformly dispersed in the matrix, wherein the ATO / TiO2 composite nanoparticles are nanocomposite powders in which both ATO and TiO2 components have hollow sphere structures. x The amount of Mg(OF) added to the matrix is x 0.1~0.2wt% of the matrix.
[0008] Furthermore, the transparent heat-insulating coating can have a transmittance of more than 85% based on a glass substrate; its heat-insulating property is manifested as follows: under the same thermal radiation conditions, the temperature inside the device isolated by the ATO / TiO2 / Mg(OF)x transparent heat-insulating coating is about 10°C lower than that inside the device isolated by bare glass only.
[0009] Furthermore, the average particle size of the ATO / TiO2 composite nanoparticles is about 50 nm.
[0010] The inventors found that Mg(OF) formed by replacing part of the fluorine in MgF2 with oxygen x The coating has good transparency and anti-reflection effect. x The coating is used as the raw material of the coating matrix, and the two-component hollow structures such as indium tin oxide (ITO), tin oxide (SnO2), zinc oxide (ZnO) are added as the heat insulation function nanoparticles of the coating. In the production process, the fine nanoparticles with two-component hollow structures can be made in Mg(OF) by selecting the raw materials and controlling the dosage. x Good dispersibility is obtained in the matrix, so that the coating produced by the present invention can obtain good heat insulation performance while maintaining the excellent transparency of the matrix as a whole, and is expected to be used in the fields of building glass curtain walls, automobile glass, etc.
[0011] The present invention also provides a method for preparing the above transparent heat-insulating coating. The technical solution adopted by the present invention is to first develop a heat-insulating functional filler, and prepare a two-component hollow structure ATO / TiO2 composite nanopowder by a hydrothermal method and a template-free method. Secondly, a transparent Mg(OF) x Anti-reflective coating technology, by controlling the amount of magnesium acetate and other materials to prepare magnesium oxyfluoride Mg (OF) x Then in magnesium oxyfluoride Mg(OF) x Adding heat-insulating nanoparticles, namely ATO / TiO2 composite nanopowder, to the matrix, and controlling the amount of diethylenetriamine, the ATO / TiO2 composite nanopowder in Mg(OF) x The dispersion of the colloid can be controlled by controlling the content of polyethylene glycol. xThe viscosity and leveling properties of the colloid form Mg(OF) with good dispersion of ATO / TiO2 powder x The colloid is prepared into the above-mentioned transparent heat-insulating coating, and a coating with high transparency and good heat-insulating effect is obtained.
[0012] Specifically, the steps for preparing the above-mentioned transparent heat-insulating coating are as follows.
[0013] Step 1: Using hydrochloric acid, anhydrous ethanol and deionized water as raw materials, mix them in a volume ratio of anhydrous ethanol:deionized water = 10:1 and hydrochloric acid:deionized water = (4-8):15, and stir them evenly to prepare an acidic solution.
[0014] Step 2: Add SnCl4 5H2O and SbCl3 to the acidic solution of step 1 in sequence according to the molar ratio of Sn:Sb=10:1, so that the concentration of Sn reaches 0.065 mol / L, and stir magnetically at room temperature for 1 hour to obtain a first mixed solution.
[0015] Step 3: The first mixed solution in step 2 is transferred to a high-temperature reactor and reacted at 200° C. for 12 hours. After the reaction, the solution is centrifuged, washed and dried to obtain Sb-doped SnO2 powder, which is recorded as product ATO.
[0016] Step 4: Using isopropyl alcohol and diethylenetriamine (DETA) as raw materials, stirring evenly to form a mixed solution, mixing according to a volume ratio of isopropyl alcohol:DETA=65:(0.5-1), and stirring evenly to form a second mixed solution.
[0017] Step 5: The second mixed solution in step 4 is added with the ATO powder in step 3 at a mass ratio of isopropanol:ATO=(250-450):1 under stirring, and stirred at room temperature for 30 minutes to obtain a uniform solution.
[0018] Step 6: Add tetrabutyl titanate (TBOT) to the solution of step 5 in an amount such that the volume ratio of TBOT to isopropanol in the solution of step 5 is (0.5-2):200, and stir at room temperature for 1 hour to obtain a third mixed solution.
[0019] Step 7: Transfer the third mixed solution in step 6 to a high-temperature reactor and react at 200° C. for 24 hours. After the reaction, centrifuge, wash and dry the solution to obtain a two-component ATO / TiO2 nanocomposite powder with a hollow structure.
[0020] Step 8: Using magnesium acetate (Mg(CH3COO)2·4H2O), trifluoroacetic acid and deionized water as raw materials, the mass ratio of magnesium acetate: trifluoroacetic acid: deionized water = 1: (2-3): 50 is mixed at 80°C to obtain a clear solution, which is then dried at 70°C to obtain a solid substance, recorded as MF.
[0021] Step 9: The MF obtained in step 8 is mixed with magnesium acetate (Mg(CH3COO)2·4H2O) and deionized water at room temperature to obtain a transparent solution. The mixing ratio is (the sum of the mass of MF and magnesium acetate): the mass ratio of water is 1:(25-50), wherein the weight ratio of MF to magnesium acetate (Mg(CH3COO)2·4H2O) is (0.20-0.25):1.
[0022] Step 10: Add diethylenetriamine and polyethylene glycol to the transparent solution obtained in step 9 to form a sol with a certain viscosity, i.e., Mg(OF) x Sol; wherein the amount of diethylenetriamine is Mg(OF) x 1% of the mass of the sol; the molecular weight of polyethylene glycol is 4000, and the amount is Mg(OF) x 10% of the mass of the sol.
[0023] Step 11: Add the ATO / TiO2 nanocomposite powder prepared in step 7 to Mg(OF) x The sol was uniformly mixed after magnetic stirring at 80° C. for 8 h; wherein the mass ratio of ATO / TiO2 nanocomposite powder to Mg(OF)x sol was (0.1-0.2):100.
[0024] Step 12: Mix the sol Mg(OF) mixed with the ATO / TiO2 nanocomposite powder in step 11 x ATO / TiO2 / Mg(OF)x transparent heat-insulating coating was obtained by coating on a glass substrate with a square coating machine, drying at 150°C, and sintering at 400-450°C in air for 40 minutes. The coating machine controlled the thickness of the obtained colloidal film to be about 1μm, and the thickness of the coating after sintering was about 150nm.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The transparent heat-insulating coating of the present invention adopts antimony-doped tin oxide (ATO) and is compounded with TiO2 to form a two-component composite nano hollow sphere structure of ATO / TiO2, which has good scattering performance and thermal stability. The two-component composite increases the specific surface area of the ATO functional filler, making ATO / TiO2 in the sol Mg(OF) xThe dispersion uniformity and stability in the coating are improved, and the agglomeration is reduced. This overcomes the poor dispersion problem of single-component indium tin oxide (ITO) and titanium oxide (TiO2) in the coating to a certain extent. The improvement in dispersion improves the transparency of the thermal insulation coating and also enables the thermal insulation filler to achieve good thermal insulation performance when used in small amounts (about 0.1-0.2% of the mass of the substrate).
[0027] 2. At the same time, the present invention controls the amount of raw materials used in the hydrothermal method, that is, through a relatively dilute solution method, to obtain ATO / TiO2 with relatively small particle size, and at the same time disperses it by adding diethylenetriamine (DETA). This makes the final transparent heat-insulating coating have two major advantages: a) because the particle size is small and does not agglomerate, only about 0.1wt% of the amount needs to be added to have a good heat-insulating effect; b) because the amount is small, the transparency of the coating is good.
[0028] 3. The present invention introduces a two-component hollow structure when preparing ATO / TiO2. Compared with a solid structure, the hollow structure has a lower thermal conductivity, so that the heat absorbed by the ATO / TiO2 microspheres is transferred slowly, which is beneficial to reduce heat transfer and improve thermal insulation performance.
[0029] 4. The Mg(OF)x coating substrate developed by the present invention has a good anti-reflection effect, controls the colloid thickness to 1 μm, and the thickness after sintering is about 150 nm, making full use of the half-wave loss mechanism, thereby improving the transparency of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a light transmittance analysis chart of the ATO / TiO2 / Mg(OF)x transparent thermal insulation coating in implementation case 1.
[0031] Figure 2 This is the SEM image of the ATO / TiO2 hollow nanospheres in implementation case 1.
[0032] Figure 3 This is the TEM image of ATO / TiO2 hollow nanospheres in implementation case 1.
[0033] Figure 4 ATO / TiO2 / Mg(OF) in implementation case 1 X Surface morphology of the coating samples.
[0034] Figure 5 ATO / TiO2 / Mg(OF) in implementation case 1 X Analysis chart of thermal insulation performance of coating samples. DETAILED DESCRIPTION
[0035] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0036] In a specific embodiment of the present invention, a specific preparation method of a transparent heat-insulating coating based on a glass substrate is provided, which takes into account both transparency and heat-insulating effects to form a coating with high transmittance and high heat-insulating effect, and is specifically implemented according to the following steps.
[0037] 1) Preparation of ATO / TiO2 hollow nanospheres
[0038] ATO / TiO2 composite nanopowder with a two-component hollow sphere structure was prepared by a hydrothermal method and a template-free method. In this process, by controlling the concentration of the process reaction solution, ATO / TiO2 composite nanoparticles with a smaller particle size were obtained, and by controlling the process parameters, ATO / TiO2 composite nanoparticles with a nano hollow sphere structure of both components were obtained without a template.
[0039] 2) Preparation of Mg(OF) x The coating matrix is prepared by controlling the amount of magnesium acetate and the like to prepare magnesium oxyfluoride Mg (OF) x Colloid, Mg(OF) can be controlled by controlling the content of polyethylene glycol x The viscosity and leveling properties of the colloid.
[0040] 3) In magnesium oxyfluoride Mg(OF) x Add thermal insulation functional material ATO / TiO2 composite nanopowder into the matrix, and control the dosage of diethylenetriamine to improve the ATO / TiO2 composite nanopowder in Mg(OF) x Colloid dispersion; and form ATO / TiO2 powder with good dispersion of Mg(OF) x colloid.
[0041] Example 1
[0042] First, 2 ml of hydrochloric acid was added to a mixed solution of 6 ml of deionized water and 60 ml of anhydrous ethanol and stirred evenly, then 0.562 g of SnCl4·5H2O and 0.038 g of SbCl3 were added to the mixed solution, and then magnetically stirred for 1 hour at room temperature. The mixed solution was transferred to a 100 mL reactor and kept at 200 ° C for 12 hours. After the reaction, the solution was centrifuged, washed and dried to obtain ATO hollow nanospheres.
[0043] Secondly, 0.5 ml of DETA was dispersed in 33 mL of isopropanol, and 0.1 g of ATO hollow nanospheres were added under stirring, and stirred at room temperature for 30 minutes. Then 0.1 ml of butyl titanate TOBT was added dropwise to the mixed solution, stirred at room temperature for 1 hour, and then transferred to a 50 mL reactor and kept at 200 ° C for 24 hours to prepare ATO@TiO2 microspheres. The product was centrifuged, washed and dried to obtain a two-component ATO / TiO2 nanocomposite powder with a hollow structure.
[0044] Then, 6g of magnesium acetate, 15g of trifluoroacetic acid and 300ml of deionized water were stirred at 80°C to obtain a clear solution, and then dried at 70°C to obtain a transparent solid substance MF for standby use. At room temperature, 1g of magnesium acetate (Mg(CH3COO)2·4H2O) and 0.22g of MF were stirred and dissolved in 40ml of deionized water to obtain a transparent solution, and 0.45g of diethylenetriamine and 4.5g of polyethylene glycol were added to the transparent solution, and stirred to obtain a uniformly dispersed Mg(OF)x sol with a certain viscosity.
[0045] Finally, use ethanol to carry out necessary cleaning and surface treatment on the glass substrate, take the ATO / TiO2 nanocomposite powder prepared above, add it to the Mg(OF)x sol, the mass ratio of ATO / TiO2 nanocomposite powder to Mg(OF)x sol is 0.1:100, and mix evenly after magnetic stirring at 80°C for 8h; use a scraper-type flatbed coater to coat it on the glass substrate, control the scraper to make the coating thickness about 1μm, dry it at 150°C, and sinter it at 400-450°C in air for 40 minutes. The coating thickness after sintering is about 150nm, and an ATO / TiO2 / Mg(OF)x transparent thermal insulation coating is obtained.
[0046] Example 2
[0047] 1.6 ml of hydrochloric acid was added to a mixed solution of 6 ml of deionized water and 60 ml of anhydrous ethanol and stirred evenly. Then 0.289 g of SnCl4·5H2O and 0.019 g of SbCl3 were added to the mixed solution and then magnetically stirred for 1 hour at room temperature. The mixed solution was transferred to a reactor and kept at 200 ° C for 12 hours to complete the reaction to generate ATO microspheres. Secondly, 0.35 ml of DETA was dispersed in 40 mL of isopropanol, and 0.08 g of ATO microspheres were added under stirring and stirred at room temperature for 30 minutes. Then 0.3 ml of TOBT was added dropwise to the mixed solution, which was then transferred to a 50 mL reactor and kept at 200 ° C for 24 hours to prepare ATO@TiO2 microspheres. The product was centrifuged, washed and dried to obtain ATO / TiO2 composite hollow powder.
[0048] Then, 7.239 g of magnesium acetate, 16.087 g of trifluoroacetic acid and 360 ml of deionized water were stirred at 80 ° C to obtain a clear solution, and then dried at 70 ° C to obtain a transparent substance MF for standby use. 1.423 g of magnesium acetate and 0.25 g of MF were stirred and dissolved in 80 ml of deionized water at room temperature to obtain a mixed solution. 0.82 g of diethylenetriamine and 8.2 g of polyethylene glycol were added and stirred to obtain a uniformly dispersed Mg(OF)x sol.
[0049] Finally, ethanol was used to carry out necessary cleaning and surface treatment on the glass substrate, and ATO / TiO2 powder was added to the above Mg(OF)x sol. The mass ratio of ATO / TiO2 nanocomposite powder to Mg(OF)x sol was 0.1:100. It was coated on the glass substrate with a scraper-type flat coater. The scraper was controlled to prepare a thickness of 1 μm. After drying at 150°C and sintering at 400-450°C in air for 40 minutes, an ATO / TiO2 / Mg(OF)x transparent thermal insulation coating was obtained.
[0050] Example 3
[0051] 2.4 ml of hydrochloric acid was added to a mixed solution of 6 ml of deionized water and 60 ml of anhydrous ethanol and stirred evenly, and then 0.219 g of SnCl4·5H2O and 0.020 g of SbCl3 were added to the mixed solution, and then magnetically stirred for 1 hour at room temperature. The mixed solution was transferred to a reactor and kept at 200°C for 12 hours to complete the reaction and generate ATO microspheres.
[0052] Secondly, 0.2 ml of DETA was dispersed in 26 mL of isopropanol, and 0.08 g of ATO microspheres were added under stirring, and stirred at room temperature for 30 minutes. Then 0.25 ml of TOBT was added dropwise to the mixed solution, and then it was transferred to a 50 mL reactor and kept at 200 ° C for 24 hours to prepare ATO@TiO2 microspheres. The product was centrifuged, washed and dried to obtain ATO / TiO2 composite hollow powder.
[0053] Then, 5.239 g of magnesium acetate, 15.876 g of trifluoroacetic acid and 265 ml of deionized water were stirred at 80 ° C to a clear solution, and then dried at 70 ° C to obtain MF. 2.36 g of magnesium acetate and 0.6 g of MF were stirred and dissolved in 75 ml of deionized water at room temperature to obtain a mixed solution. Then 0.78 g of diethylenetriamine and 7.80 g of polyethylene glycol were added to the mixed solution and stirred to obtain a uniformly dispersed Mg(OF)x sol.
[0054] Finally, ethanol was used to clean and surface treat the glass substrate as necessary, and ATO / TiO2 was added to the Mg(OF)x sol above. The mass ratio of ATO / TiO2 nanocomposite powder to Mg(OF)x sol was 0.1:100. It was coated on the glass substrate with a scraper-type flat coater. The scraper was controlled to prepare a thickness of 1 μm. After drying at 150°C and sintering at 400-450°C in air for 40 minutes, an ATO / TiO2 / Mg(OF)x transparent thermal insulation coating was obtained.
[0055] Example 4
[0056] 2.4 ml of hydrochloric acid was added to a mixed solution of 4.5 ml of deionized water and 60 ml of anhydrous ethanol and stirred evenly, and then 0.219 g of SnCl4·5H2O and 0.020 g of SbCl3 were added to the mixed solution, and then magnetically stirred for 1 hour at room temperature. The mixed solution was transferred to a reactor and kept at 200°C for 12 hours to complete the reaction and generate ATO microspheres.
[0057] Secondly, 0.4 ml of DETA was dispersed in 52 mL of isopropanol, and 0.08 g of ATO microspheres were added under stirring, and stirred at room temperature for 30 minutes. Then 0.13 ml of TOBT was added dropwise to the mixed solution, and then it was transferred to a 50 mL reactor and kept at 200 ° C for 24 h to prepare ATO@TiO2 microspheres. The product was centrifuged, washed and dried to obtain ATO / TiO2 composite hollow powder.
[0058] Then, 5.24 g of magnesium acetate, 10.45 g of trifluoroacetic acid and 265 ml of deionized water were stirred at 80° C. to a clear solution, and then dried at 70° C. to obtain MF. 2.36 g of magnesium acetate and 0.6 g of MF were stirred and dissolved in 148 ml of deionized water at room temperature to obtain a mixed solution. Then, 1 wt.% of diethylenetriamine and 10.0 wt.% of polyethylene glycol based on the mass of the Mg(OF)x sol were added to the mixed solution, and stirred to obtain a uniformly dispersed Mg(OF)x sol.
[0059] Finally, ethanol was used to clean and surface treat the glass substrate as necessary, and ATO / TiO2 was added to the Mg(OF)x sol above. The mass ratio of ATO / TiO2 nanocomposite powder to Mg(OF)x sol was 0.2:100. It was coated on the glass substrate with a scraper-type flat coater. The scraper was controlled to prepare a thickness of 1 μm. After drying at 150°C and sintering at 400-450°C in air for 40 minutes, an ATO / TiO2 / Mg(OF)x transparent thermal insulation coating was obtained.
[0060] ATO / TiO2 / Mg(OF) prepared in each embodimentx The transparent heat insulation coating has high transparency and looks similar to the original glass substrate when observed with the naked eye. The light transmittance is tested as follows: Figure 1 The transmittance graph of the coating obtained in Example 1, in which the three curves "glass", "glass / Mg(OF) x "ATO / TiO2 / Mg(OF)x" are glass substrate, pure Mg(OF) formed on glass substrate without adding thermal insulation functional material x Coating, and the transmittance of the ATO / TiO2 / Mg(OF)x coating formed on the glass substrate at a light wavelength of 300-800nm. As can be seen from the figure, after the Mg(OF)x coating is prepared on the glass substrate, the transparency of the glass is improved to a certain extent; after ATO / TiO2 composite hollow sphere nanoparticles are further added to Mg(OF)x, after the ATO / TiO2 / Mg(OF)x coating is formed on the glass substrate, because the ATO / TiO2 content is only about 0.1%, the transmittance is still very high, and its visible light transmittance can still reach more than 85%, reaching a transparency close to that of glass, which is more than 6% higher than the visible light transmittance of the conventional pure ATO coating in the prior art. The other embodiments are equivalent to embodiment 1, and the visible light transmittance of the ATO / TiO2 / Mg(OF)x coating is basically above 85%.
[0061] The microscopic morphology of the ATO / TiO2 composite nanopowders prepared in each embodiment was tested, and it was confirmed that the ATO / TiO2 composite nanopowders have a microstructure of hollow nanospheres in both components, and the nanoparticles of the ATO / TiO2 composite nanopowders are uniform and the particle size is as small as about 50nm. Figure 2 and Figure 3 The SEM image and TEM image of the ATO / TiO2 powder prepared in Example 1 are shown in FIG. 1 , respectively. It can be seen that the particle size of the hollow powder is about 50 nm, which is about 4 times smaller than the size of conventional nanoparticles of this type, which is usually about 200 nm. Therefore, the surface of the prepared coating is smooth, further improving the light and heat shielding properties of the coating. Figure 4 ATO / TiO2 / Mg(OF) prepared in Example 1 X The surface morphology test picture of the coating shows that the surface is flat.
[0062] The ATO / TiO2 / Mg(OF) prepared in each embodiment was tested. XThe thermal insulation performance of the coating is shown in the following examples. The ATO / TiO2 / Mg(OF)x transparent thermal insulation coating with a thickness of about 150nm on the glass substrate is 10°C lower than the bare glass substrate after the temperature stabilizes after 50 minutes of illumination. It can be seen that the addition of the two-component nano hollow spheres ATO / TiO2 microspheres can effectively eliminate heat conduction and achieve a thermal insulation effect. Figure 5 This is a test diagram of the thermal insulation performance of the ATO / TiO2 / Mg(OF)x transparent thermal insulation coating prepared in Example 1. The three curves in the figure are "glass", "glass / Mg(OF) x "ATO / TiO2 / Mg(OF)x" represent glass substrate, pure Mg(OF) formed on glass substrate without adding thermal insulation functional material, x The temperature changes of the device isolated by the ATO / TiO2 / Mg(OF)x coating and the ATO / TiO2 / Mg(OF)x coating formed on the glass substrate during the illumination 0-50min period are shown in Figure 2. At 50min, the temperature is basically stable. It can be seen that the temperature inside the device isolated by the ATO / TiO2 / Mg(OF)x transparent heat insulation coating is 11°C lower than that of the pure glass. The test results of other embodiments, such as the addition of 0.1wt.% ATO@TiO2 in Example 2,
[0063] The temperature inside the ATO@TiO2 / Mg(OF)x thermal insulation coating device is lower than that of pure glass.
[0064] 10.15℃; and Example 3 is 10.24℃ lower.
Claims
1. A transparent heat-insulating coating, characterized in that: The coating is magnesium oxyfluoride Mg (OF) x As the matrix, in the Mg(OF) x ATO / TiO2 composite nanoparticles are uniformly dispersed in the matrix; the ATO / TiO2 composite nanoparticles are nanocomposite powders with a two-component nano hollow sphere structure of ATO and TiO2.
2. A transparent heat-insulating coating according to claim 1, characterized in that: The ATO / TiO2 composite nanoparticles are x The amount of Mg(OF) added to the matrix is x 0.1~0.2wt% of the matrix.
3. The transparent heat-insulating coating according to claim 1, characterized in that: The coating can achieve a visible light transmittance of more than 85% based on a glass substrate; the thermal insulation of the coating is manifested as follows: under the same thermal radiation conditions, the temperature inside the device isolated by the coating is more than 10°C lower than that of the device isolated by bare glass alone.
4. The transparent heat-insulating coating according to claim 1, characterized in that: The average particle size of the ATO / TiO2 composite nanoparticles is 50 nm.
5. The method for preparing the transparent heat-insulating coating according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, using hydrochloric acid, anhydrous ethanol and deionized water as raw materials, stirring uniformly to prepare an acidic solution; adding SnCl4 5H2O and SbCl3 to the acidic solution in sequence, stirring at room temperature to obtain a first mixed solution; Step 2: The first mixed solution in step 1 is transferred to a high temperature reactor for hydrothermal reaction. After the reaction is completed, the solution is centrifuged, washed and dried to obtain Sb-doped SnO2 powder, i.e., ATO powder; Step 3, using isopropyl alcohol and diethylenetriamine DETA as raw materials, mixing and stirring to form a second mixed solution; adding the ATO powder of step 2 to the second mixed solution, stirring to form at room temperature, and then adding tetrabutyl titanate TBOT, stirring to obtain a third mixed solution; Step 4, transferring the third mixed solution to a high-temperature reactor for hydrothermal reaction, centrifuging, washing and drying after the reaction to obtain dual-component ATO / TiO2 composite nanoparticles with a hollow structure; Step 5, using magnesium acetate (Mg(CH3COO)2·4H2O), trifluoroacetic acid and deionized water as raw materials, mixing to obtain a clear solution, and then drying to obtain a solid substance, recorded as MF; Step 6: Mix the MF obtained in step 5 with magnesium acetate (Mg(CH3COO)2·4H2O) and deionized water at room temperature to obtain a transparent solution; add diethylenetriamine and polyethylene glycol to the transparent solution to form a sol with a certain viscosity, i.e., Mg(OF) x Sol; Step 7, adding the ATO / TiO2 composite nanoparticles prepared in step 4 to Mg(OF) x The sol is stirred and mixed evenly to form a coating precursor; the coating precursor is coated on a substrate, and the transparent heat-insulating coating is obtained after drying and sintering.
6. The method for preparing the transparent heat-insulating coating according to claim 5, characterized in that: In step 1: The addition of hydrochloric acid, anhydrous ethanol and deionized water satisfies the volume ratio of anhydrous ethanol: deionized water = 10:1 and hydrochloric acid: deionized water = (4-8): 15; SnCl4 5H2O and SbCl3 were added in a molar ratio of Sn:Sb=10:
1.
7. The method for preparing the transparent heat-insulating coating according to claim 5, characterized in that: In step 3: isopropyl alcohol and diethylenetriamine DETA are mixed in a volume ratio of 65:(0.5-1) to form a second mixed solution; ATO powder is added to the second mixed solution in a mass ratio of isopropyl alcohol:ATO=(250-450):1; tetrabutyl titanate is added to meet the volume ratio of isopropyl alcohol in the second mixed solution of (0.5-2):200; The hydrothermal reaction in step 4 was carried out at 200° C. for 24 h.
8. The method for preparing the transparent heat-insulating coating according to claim 5, characterized in that: In step 5: magnesium acetate (Mg(CH3COO)2·4H2O), trifluoroacetic acid and deionized water are mixed in a mass ratio of 1:(2-3):50, and the mixing temperature is 80°C.
9. The method for preparing the transparent heat-insulating coating according to claim 5, characterized in that: In step 6: The ratio of MF, Mg(CH3COO)2·4H2O and deionized water to form a transparent solution satisfies that the mass ratio of MF to Mg(CH3COO)2·4H2O and the mass ratio of MF to deionized water is 1:(25-50), wherein the weight ratio of MF to Mg(CH3COO)2·4H2O is (0.20-0.25):1; Formation of Mg(OF) x The amount of diethylenetriamine in the sol is Mg(OF) x 1% of the mass of the sol, the amount of polyethylene glycol used is Mg(OF) x 10% of the mass of the sol.
10. The method for preparing the transparent heat-insulating coating according to claim 5, characterized in that: In step 7: ATO / TiO2 composite nanoparticles are added to Mg(OF) x The coating precursor is formed by stirring in the sol at 80°C; wherein the mass ratio of ATO / TiO2 nanocomposite powder to Mg(OF)x sol is (0.1-0.2):100; the coating drying and sintering temperatures are 150°C and 400-450°C, respectively.
Citation Information
Patent Citations
Method of using sol-gel to prepare MgF2 antireflection film
CN102976626A
Preparation method of low-temperature-curing high-strength self-cleaning multi-function anti-reflective film
CN108706888A
Preparation method of composite nano-powder and coating for preparing antireflection and transparent heat-insulating coating
CN112521775A
Photovoltaic self-cleaning nano coating with heat insulation and antistatic functions and preparation method thereof
CN118772669A
Method for the manufacture of magnesium fluoride sols and magnesium fluoride sol
EP2540667A1
Cited By
Preparation method of high-strength and high-thickness heat insulation ceramic coating for polar region ship pipeline
CN121446696A
